2021
DOI: 10.1002/pat.5562
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterials as additives to ethylene vinyl acetate copolymer foams for sport footwear applications

Abstract: Ethylene vinyl acetate (EVA) copolymer foams with addition of 1.0, 2.5, and 5 wt% of carbon nanomaterials (graphene, graphene oxide, carbon nanotubes, and multiwalled carbon nanotubes) were fabricated. Properties of these foams were compared with reference sample (no additives) and samples containing carbon black. The following properties of these samples were examined: density, compressive stress (50% compression), impact behavior, thermal conductivity, and hydrophobicity. The morphology was studied using sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The shoe industry is a huge and rapidly developing industry [ 28 ]. According to statistics, the worldwide footwear market was evaluated to be worth 373 billion USD in 2021, and that value is set to reach 430 billion USD in 2030 [ 29 , 30 ]. With the rapid development of the shoe industry, polymeric foam waste has also increased considerably [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shoe industry is a huge and rapidly developing industry [ 28 ]. According to statistics, the worldwide footwear market was evaluated to be worth 373 billion USD in 2021, and that value is set to reach 430 billion USD in 2030 [ 29 , 30 ]. With the rapid development of the shoe industry, polymeric foam waste has also increased considerably [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the polymer filled with CNT composite foam studies thus far are not focused on the dynamic impulse rebound (energy return) and the dynamic response of the foam, particularly for EVA foam used for sportswear midsole application. In our previous works, we found that carbon-based nanomaterials including carbon black, graphene, and CNTs have properties desirable in developing high-performance foam for sport footwear soles when used as reinforcing fillers [ 20 ]. EVA filled with a very low content of graphene shows a striking improvement of approximately 30% increase of stiffness, superior abrasion resistance, and better-cushioning property as compared to the reference sample, which is the desire for running shoes in terms of energy repulsion [ 21 ].…”
Section: Introductionmentioning
confidence: 99%